Strengthening strategy for a ductile metastable β-titanium alloy using low-temperature aging. Issue 8 (15th November 2017) - Sun, F.; Zhang, J. Y.; Vermaut, P.; Choudhuri, D.; Alam, T.; Mantri, S. A.; Svec, P.; Gloriant, T.; Jacques, P. J.; Banerjee, R.; Prima, F.
ABSTRACT: While ω precipitates in metastable β titanium alloys are typically considered embrittling and consequently deleterious to the mechanical properties, this paper demonstrates that low-temperature aging (LTA) treatments for short time periods can in fact enhance the yield strength while preserving substantial elongation-to-failure in ω containing β titanium alloys. LTA treatments, carried out on a ductile β metastable Ti–12Mo alloy, significantly improve the yield strength of the material (∼55% increase as compared to solution-treated samples) while keeping both TRIP/TWIP effects and a large elongation-to-failure ( ϵ  = 0.4 in true strain), resulting in a balance of mechanical properties. IMPACT STATEMENT Employing a novel low-temperature annealing strategy, omega precipitates, typically considered embrittling in beta titanium alloys, can effectively increase the yield strength by 50% while preserving 40% tensile ductility. GRAPHICAL ABSTRACT: